Impact of cocaine abuse on HIV pathogenesis - Dash, Sabyasachi; Balasubramaniam, Muthukumar; Villalta, Fernando; Dash, Chandravanu; Pandhare, Jui (Frontiers in Microbiology, 2015)
Over 1.2 million people in the United States are infected with the human immunodeficiency virus (HIV). Tremendous progress has been made over the past three decades on many fronts in the prevention and treatment of HIV-1 disease. However, HIV-1 infection is incurable and antiretroviral drugs continue to remain the only effective treatment option for HIV infected patients. Unfortunately, only three out of ten HIV-1 infected individuals in the US have the virus under control. Thus, majority of HIV-1 infected individuals in the US are either unaware of their infection status or not connected/retained to care or are non-adherent to antiretroviral therapy (ART). This national public health crisis, as well as the ongoing global HIV/AIDS pandemic, is further exacerbated by substance abuse, which serves as a powerful cofactor at every stage of HIV/AIDS including transmission, diagnosis, pathogenesis, and treatment. Clinical studies indicate that substance abuse may increase viral load, accelerate disease progression and worsen AIDS-related mortality even among ART adherent patients. However, confirming a direct causal link between substance abuse and HIV/AIDS in human patients remains a highly challenging endeavor. In this review we will discuss the recent and past developments in clinical and basic science research on the effects of cocaine abuse on HIV-1 pathogenesis.